SUBSTANTIATION OF THE DESIGN OF BAKING OVENS WITH RECIRCULATION OF COMBUSTION PRODUCTS - Федорів, Віктор; Люховець, Володимир; Маньков, Віктор; Степанець, Олексій (Modern engineering and innovative technologies, 2024)
The article deals with the problems of the influence of rational operating modes of baking ovens, which is an important task of the oven operation for significant fuel savings. In bakery ovens, one of the main quantities most sensitive to load changes is